2022
DOI: 10.3389/fpls.2022.824461
|View full text |Cite
|
Sign up to set email alerts
|

Varying Relationship Between Vascular Plant Leaf Area and Leaf Biomass Along an Elevational Gradient on the Eastern Qinghai-Tibet Plateau

Abstract: The altitudinal gradient is one of the driving factors leading to leaf trait variation. It is crucial to understand the response and adaptation strategies of plants to explore the variation of leaf traits and their scaling relationship along the altitudinal gradient. We measured six main leaf traits of 257 woody species at 26 altitudes ranging from 1,050 to 3,500 m within the eastern Qinghai-Tibet Plateau and analyzed the scaling relationships among leaf fresh weight, leaf dry weight, and leaf area. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(89 reference statements)
2
1
0
Order By: Relevance
“…, 2020) further augmented by high plant density (Table 1) in line with other works (Yang et al. , 2022). Other factors could also be involved, such as increased leaf sugar accumulation and decreasing specific leaf area which has been reported in leaves developed under lower T (Riva-Roveda et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…, 2020) further augmented by high plant density (Table 1) in line with other works (Yang et al. , 2022). Other factors could also be involved, such as increased leaf sugar accumulation and decreasing specific leaf area which has been reported in leaves developed under lower T (Riva-Roveda et al.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with this, specific leaf area is decreased in leaves developed at low T (Riva-Roveda et al, 2016;Zhou et al, 2020) and in maize lines from cool temperate regions compared with lines from warmer origin (Verheul et al, 1996). Increased light penetration in the canopy could explain the thicker leaves at ERO, whereas, at HOR, increased shading resulted in higher specific leaf area (Yabiku et al, 2020) further augmented by high plant density (Table 1) in line with other works (Yang et al, 2022). Other factors could also be involved, such as increased leaf sugar accumulation and decreasing specific leaf area which has been reported in leaves developed under lower T (Riva-Roveda et al, 2016).…”
Section: Leaf Traitssupporting
confidence: 89%
“…In fact, our treatments were a canopy-shading gradient for bamboo (i.e., BC < CB < CS < FC, Table 4). Unlike more experiments [43], bamboo leaf traits of our study showed a unimodal curve with the gradient rather than a linear relationship, which is consistent with the leaf anatomical traits at levels of plant functional group from eastern China [44], and vascular plant leaf area vs. leaf biomass within the Bailongjiang from northwestern China [45].…”
Section: Discussionsupporting
confidence: 83%
“…The following traits were measured in this test: embryonic axis diameter (stem diameter measured using Vernier callipers) (Yang et al, 2022b), maximum root length (a straightedge was used to measure the maximum length of the root), plant height (measured from the ground to the top of the plant using a straightedge), root fresh weight (the roots were removed, dried on paper towels, and weighed on an electronic balance), leaf fresh weight (all leaves were cut off and weighed on an electronic balance), root dry weight (roots were dried in a ventilated oven at 105 °C for 15 min, then transferred to 75 °C for drying to a standard weight) (Polash et al, 2018), and leaf dry weight (leaves were dried in a ventilated oven at 105 °C for 15 min, then transferred to 75 °C for drying to a standard weight) (Yang et al, 2022a). Related tools were Vernier callipers (0.01 mm, Brand: Sheffield, Model: S071012, Origin: Mainland China), electronic balance (0.00001 g, Brand: Mettler-Toledo GmbH, Model: MS105DU/A, Origin: Switzerland), and steel ruler (0.1 cm, Brand: Sheffield, Model: S079020, Origin: China Mainland).…”
Section: Phenotype Identification and Physiological Trait Assaymentioning
confidence: 99%